LIFESTYLE RISK FACTORS AND BONE MASS IN RECURRENT STONE-FORMING PATIENTS: A CROSS-SECTIONAL STUDY IN 144 SUBJECTS - Marić, Ivana (Acta Clin Croat, 2019)
Patients with urolithiasis, particularly hypercalciuria, may have reduced bone mineral density (BMD). There are numerous risk factors contributing to reduction of BMD such as advanced age, sedentary lifestyle, smoking, low calcium intake, etc. The aim of our study was to investigate the association of lifestyle risk factors and daily intake of milk and dairy products with determinants of BMD in a group of recurrent calcium stone formers (RSF) compared with healthy subjects (HS). The study was carried out at the Department of Mineral Research, Faculty of Medicine in Osijek, Croatia. The study included 144 subjects, i.e. 56 RSF and 78 HS. BMD was assessed by dual-energy x-ray absorptiometry. A standard self-reported questionnaire was used to collect data on lifestyle risk factors. Current dietary intake was assessed by personal interview that included questions about milk and dairy product intake. Low BMD was observed in 44.64% of RSF and 35.90% of HS. RSF consumed significantly less milk and dairy products than HS. Calcium restriction in dietary recommendations might be unnecessary due to the impact on bone mineral loss in RSF and dual-energy x-ray absorptiometry should be included in the routine evaluation of RSF.